Transgressions and Reterritorializations as Markers of Minor Literature in Kurt Vonnegut’s Slapstick, or Lonesome no More! - Mengouchi, Meryem; Mouro, Wassila Hamza Reguig (Hungarian Journal of English and American Studies, 2021)
Deterritorialization and reterritorialization are transgressive techniques in literature that characterize subversive literature. Gilles Deleuze and Félix Guattari suggest that questions about marginal literature or other forms of peripheral literatures must all be covered within the designation and definition of minor literature, not only if they are written in the language of the mainstream. Kurt Vonnegut’s Slapstick, or Lonesome no More (1976) is a set of deterritorializations and reterritorializations made possible through creative assemblage, a technique that allows a continuous flow of meaning, that is, meaning is not fixed, as language moves from one territory to another, constructing new assemblages and acquiring new meanings. Meaning changes each time a new assemblage is composed. Through the re-construction of family, love, and human relationships, the novel defies the alienating practices of the American society as presented in Vonnegut’s novel. (MM and WHRM)